Modern database management - Hoffer, J. A. Jeffer A. Hoffer; Ramesh, V. V. Ramsher; Topi, H. Heikki Topi (Boston: Pearson, 2011)
Reacting to the business environment, this work addresses issues such as Internet, data warehousing and object-orientation. The text instructs from a business perspective, allowing students to understand database management within a business
Includes appendices, glossary and indexes
Keywords: Data warehousing; Database design; Database management; Informatics